Socio-Environmental (In)Justice in Forest Stewardship: A Multi-Perspective Materials Assemblage for English as a Foreign Language Teacher Education in Chile - Farias-Farias, M (Taylor and Francis, 2024)
With UNESCO s (2017, 2021) learning objectives for Education for Sustainable Development (ESD) goals in mind, this chapter makes a proposal for a content-based literacy project around the topic of forest stewardship. It includes a multi-perspective assemblage of authentic materials on sustainable forestry revealing global connections and contradictions leading to socio-environmental injustices. By contrasting Indigenous perspectives on humans’ role of nature stewardship with the normalised practices of a throwaway consumerist economy, the proposal hopes to contribute to restoring a caring relationship with Mother Earth. The materials include “detective work” tasks for students to discover shared responsibilities in malfunctioning forest stewardship in Southern Chile, global interconnections in the production and consumption of wood products and mechanisms of epistemic violence against Indigenous knowledge. This chapter presents findings from a pilot application of these materials in a pre-service teacher education programme in Chile. © 2025 selection and editorial matter, Nicholas McGuinn and Amanda Naylor.